The Methodology of the Biomechanical Movements for the Disabled Based on Art Therapy - Ivana Zidek; Jana Musinska; Jozef Zivcak (Communications, 2015)
The essence of the research work is to open up the new possibilities in the treatment processes within rehabilitation, physiotherapy and consequent movement re-education process for people with disabilities, post-traumatic conditions, or degenerative disease. Art therapy is a special type of psychotherapy that focuses on the development of creative skills, emotional development and interpersonal relationships of the mentally, physically or socially disturbed individuals. The methodology proposal includes the systems of rehabilitation, therapeutic physical education, physiotherapy, and ergotherapy. The purpose of the methodology of the biomechanical movements using art therapy is to follow and build on the classic rehabilitation of the patients with physical disabilities. The aim of this form of therapy is to increase the strength of weakened muscles and the range of joint movement, to improve the neuromuscular coordination, and to improve the physical independence of the physically disabled individuals.